Astrometry-only detection of microlensing events with Gaia - Jankovič, Taj; Gomboc, A.; Wyrzykowski, Ł.; Kostić, U.; Karlica, M.; Larma, M.; Petrushevska, T.; Bronikowski, M.; Jabłońska, M.; Kaczmarek, Zofia (Astronomy and astrophysics, 2025)
Methods. We generated mock Gaia observations for different magnitudes, different numbers of Gaia visits, and events extending beyond Gaia’s observational run. We applied GAME Filter to these datasets and validated its performance. We also assessed the rate of false positives involving binary astrometric systems misidentified as microlensing events. - Results. GAME Filter successfully recovers microlensing parameters for strong events. Parameters are more difficult to recover for short events and those extending beyond Gaia’s run, where only a fraction of the events are observed. The astrometric effect breaks the degeneracy in the microlensing parallax present in photometric microlensing. For fainter sources, the observed signal weakens, reducing recovered events and increasing parameter errors. However, even for Gaia G-band magnitude 19, the parameters can be recovered for Einstein radii ≳2 mas. Observing regions with varying numbers of Gaia visits has a minimal impact on filter accuracy when the number of visits is ≳90. Additionally, even if the peak of a microlensing event lies outside Gaia’s run, microlensing parameters can still be recovered. GAME filter characterises lenses with astrometry-only data for lens masses ranging from approximately 1-20 M⊙ and distances of up to ≈6 kpc. - Conclusions. GAME Filter reveals the astrometric potential in microlensing events. Our results indicate that astrometric data can enhance photometric detections and refine constraints on microlensing parameters.
Gesehen am 20.01.2026